Expression of the Longest RGS4 Splice Variant in the Prefrontal Cortex Is Associated with Single Nucleotide Polymorphisms in Schizophrenia Patients - Ding, Lan; Styblo, Miroslav; Drobná, Zuzana; Hegde, Ashok N. (Frontiers in Psychiatry, 2016)
The Regulator of G protein signaling 4 (RGS4) gene is a candidate susceptibility gene for schizophrenia (SCZ). Previous studies showed that the mRNA level of the longest splice variant RGS4-1 was decreased in the dorsolateral prefrontal cortex (DLPFC) of SCZ patients compared with healthy controls. In this pilot study, we examined the possible mechanisms of RGS4-1 mRNA reduction in SCZ. We genotyped SNP1 (rs10917670), rs2661347, SNP4 (rs951436), SNP7 (rs951439), SNP18 (rs2661319), and rs10799897 (SNP9897) and tested the methylation status of CpG islands of the RGS4 gene in the postmortem DLPFC samples obtained from subjects with SCZ and bipolar disorder (BPD) as well as healthy controls. RGS4-1 mRNA level was associated with five SNPs (SNP1, rs2661347, SNP4, SNP7 and SNP18) and their haplotypes but not with SNP9897. In addition, this study revealed that RGS4-1 mRNA was low in subjects with specific genotypes of SNP1, rs2661347, SNP4, SNP7, and SNP18. Lower RGS4-1 mRNA expression in the DLPFC of SCZ is associated with SNPs in the 5’ regulatory region of the RGS4 gene but not with the methylation status of its CpG islands.